Development and characterization of postbiotic-enriched biodegradable films with antifungal activity for tomato storage - Kaya, Yasemin; Ispirli, Humeyra; Bozkurt, Fatih; Sagdic, Osman; Sengul, Mustafa; Dertli, Enes (WILEY, 2026)
BACKGROUND One of the major contributors to postharvest losses in tomatoes is the development of infectious mold diseases. In this study, four distinct biodegradable film formulations were developed incorporating postbiotics derived from Lactiplantibacillus plantarum Y48 and the polysaccharide alternan. The formulations included alternan, sodium alginate and glycerol (AAG), alternan, postbiotic, sodium alginate and glycerol (APAG), postbiotic, sodium alginate and glycerol (PAG), and sodium alginate and glycerol (AG) as a control. The films were characterized in terms of their physical, mechanical, thermal, and morphological properties. To assess antifungal efficacy, tomatoes artificially inoculated with Alternaria alternata were coated with each film and stored at ambient temperature for 8 days.RESULTS The incorporation of alternan and postbiotics enhanced both the mechanical strength and thermal stability of the films. Fourier-transform infrared (FTIR) analysis confirmed the successful integration of the bioactive components into the polymer matrix. Scanning electron microscopy (SEM) imaging revealed that postbiotic addition contributed to a rougher and more rigid surface morphology, while alternan improved the structural cohesion of the films. All film formulations exhibited significant inhibitory effects against A. alternata, with the PAG formulation demonstrating the most pronounced antifungal activity.CONCLUSION These results suggest that the PAG film, enriched with postbiotics, represents a promising biocontrol strategy for mitigating fungal spoilage in tomatoes. In conclusion, this study underscores the potential of combining postbiotics and alternan for the development of active, biodegradable edible films with antifungal functionality for postharvest preservation. (c) 2025 Society of Chemical Industry.
Keywords: alternan; Alternaria alternata; biopreservation; edible film; postbiotics; tomato storage; CELL-FREE SUPERNATANT; LACTIC-ACID BACTERIA; ANTIMICROBIAL ACTIVITY; POSTHARVEST QUALITY; PHYSICAL-PROPERTIES; BIOLOGICAL-CONTROL; EDIBLE COATINGS; PROTEIN FILMS; LACTOBACILLUS; FUNGAL; Agriculture; Chemistry; Food Science & Technology